Magnitude and influencing factors of parasomnia in schoolchildren - Choudhury Habibur Rasul; Khan Golam Mostafa; Nitya Nanda Baruri; Jakia Sultana (Indonesian Pediatric Society Publishing House, 2013)
Background Parasomnias are undesirable events occurring in the sleep-wake transition period. Several predisposing factors are reported to induce parasomnia in preschool children. Objective To es timate the magnitude of parasomnia in school children and to evaluate its relationship with possible predisposing factors . Methods Five hundred children aged 5- 16 years from a boys' school and a girls' school in Khulna City, Ban gladesh, were randomly selected for the study conducted fromJuly to December 2011. The survey was don e in two steps: self-administered questionnaire and clinical interviews of affected students and their parents. Apart from demographic features, questionnaires included details of perinatal and personal fac tors as well as familial and socioeconomic factors . The diagnoses of variants of parasomnias was based on the criteria for category-based classification by the American Academy of Sleep Medicine. Results Seven hundred thir teen filled questionnaires revealed parasomnia in 187 (26.2%) children. Most parasomnias were accompanied by other sleep disorders, in which 23 (12.3%) having primary dyssomnias including 18 (9.3%) obstructive sleep apnea, and 10 (5.3%) parasomnias with hypersomnias . Nightmares (7. 4%) were highest among the parasomnias fo llowed by nocturnal enuresis (4.1 %) and sleep terrors (3 .4%). More girls experienced parasomnias than boys (107 /360 vs . 80/353, respectively; P= 0.039) . Perinatal factors such as problems during pregnancy (17 .1 %) or eventful delivery (25. 7%), and socioeconomic factors such as familial disharmony (11.8%) and low socioeconomiclevel (3 1.6%) had positive associations with parasomnia. Conclusion One-quarter of school children experience parasomnia. We found perinatal factors particularly problem during pregnancy, and socioeconomic factors particularly familial disharmony have significant influences on this condition.